2000
DOI: 10.1530/eje.0.1430687
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of dehydroepiandrosterone and dexamethasone on the generation of monocyte-derived dendritic cells

Abstract: Background: Dehydroepiandrosterone (DHEA) has been suggested as an immunostimulating steroid hormone, of which the effects on the development of dendritic cells (DC) are unknown. The effects of DHEA often oppose those of the other adrenal glucocorticoid, cortisol. Glucocorticoids (GC) are known to suppress the immune response at different levels and have recently been shown to modulate the development of DC, thereby influencing the initiation of the immune response. Variations in the duration of exposure to, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 50 publications
(36 reference statements)
5
41
0
2
Order By: Relevance
“…DEXAMETHASONE AND NEONATAL DENDRITIC CELLS a counterbalancing Th1 cytokine, confirms the work of others (29,33,34,44). The observation that Dx added to CB cells during the differentiation stage dramatically amplified the modulation compared with AB cells extends previous observations (Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…DEXAMETHASONE AND NEONATAL DENDRITIC CELLS a counterbalancing Th1 cytokine, confirms the work of others (29,33,34,44). The observation that Dx added to CB cells during the differentiation stage dramatically amplified the modulation compared with AB cells extends previous observations (Fig.…”
supporting
confidence: 90%
“…The results suggest that Dx is instrumental in sustaining macrophage-like cells in CB cultures, and these data are consistent with the hypothesis that Dx is a genomic-affecting steroid (43). Canning et al (44) reported a similar increase of CD14 expression when Dx was added during the differentiation stage in a human adult monocyte/DC culture, although Dx effect during the maturation stage was not studied.…”
mentioning
confidence: 93%
“…Currently, RA can be successfully treated with glucocorticoids (1). It has been suggested that the immunosuppressive effects of glucocorticoids may be counteracted by the naturally occurring dehydroepiandrosterone (DHEA) (2,3). More recent data, however, suggest that 7␣-hydroxy-DHEA (7␣-OH-DHEA), rather than DHEA itself, prevents the immunosuppressive effects of glucocorticoids (4).…”
mentioning
confidence: 99%
“…In rodents, DHEA antagonizes dexamethasone-induced suppression of lymphocyte proliferation and prevents glucocorticoid-induced thymic and splenic atrophy (Blauer et al ., 1991). DHEA and dexamethasone may have opposing effects on dendritic cell differentiation (Canning et al ., 2000). DHEA and the glucocorticoid receptor antagonist RU486 equally reverse the suppressive effects of glucocorticoids on immune function (Araneo & Daynes, 1995).…”
Section: Adrenal Steroidsmentioning
confidence: 99%